2016
DOI: 10.1111/geb.12500
|View full text |Cite
|
Sign up to set email alerts
|

Linking microbial C:N:P stoichiometry to microbial community and abiotic factors along a 3500‐km grassland transect on the Tibetan Plateau

Abstract: Aim To explore large‐scale patterns and the drivers of carbon:nitrogen:phosphorus (C:N:P) stoichiometry in heterotrophic microbes. Location A 3500‐km grassland transect on the Tibetan Plateau. Methods We investigated large‐scale C:N:P stoichiometry patterns in the soil microbial biomass and their relationships with abiotic factors and soil microbial community structures by obtaining soil samples from 173 sites across the Tibetan alpine grasslands. Results C:N:P ratios in the soil microbial biomass varied widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 53 publications
(114 reference statements)
4
71
1
Order By: Relevance
“…A recent global synthesis of 85 chronosequences also found that secondary succession had a rising trend in fungi to bacteria ratio (Zhou, Wang, Jiang, & Luo, ). Given the fact that it has been effectively applied in recent microbial studies (e.g., Chen, Chen, Peng et al, ; Chen, Chen, Robinson et al, ; Kaiser et al, ; Zechmeister‐Boltenstern et al, ; Zhou, Wang, Jiang et al, ), adopting the K ‐ and r ‐selection framework for microbial ecology can improve our understanding of the behaviour and responses of microbial communities to land‐use changes and global change (Ho et al, ) and their functioning in soil systems (Fierer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent global synthesis of 85 chronosequences also found that secondary succession had a rising trend in fungi to bacteria ratio (Zhou, Wang, Jiang, & Luo, ). Given the fact that it has been effectively applied in recent microbial studies (e.g., Chen, Chen, Peng et al, ; Chen, Chen, Robinson et al, ; Kaiser et al, ; Zechmeister‐Boltenstern et al, ; Zhou, Wang, Jiang et al, ), adopting the K ‐ and r ‐selection framework for microbial ecology can improve our understanding of the behaviour and responses of microbial communities to land‐use changes and global change (Ho et al, ) and their functioning in soil systems (Fierer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, primary or secondary forests are presumably more mature and undisturbed ecosystems compared with plantations or agricultural ecosystems during forest degradation. Second, we assume that microbial attributes can be described by the K ‐ and r ‐selected categories (Chen, Chen, Peng et al, ; Chen, Chen, Robinson et al, ; Fierer et al, ; Kaiser, Franklin, Dieckmann, & Richter, ; Zechmeister‐Boltenstern et al, ), similar to those used in plant and animal community ecology. Fungi tend to be K ‐strategists compared with bacteria, because they have larger size, longer turnover time, higher resource use efficiency, lower maintenance respiration to biomass ratio and higher microbial C to soil C ratio (Bailey et al, ; Six et al, ; Waring et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Li et al (2015) summarized the data and found that the microbial N : P ratio decreased with latitude. Undoubtedly, there is uncertainty in the values of microbial C : N, C : P, and N : P ratios in global studies, and the variations in these patterns might have been partially caused by the different methods that were used in the various studies (Xu et al, 2013;Chen et al, 2016). Furthermore, less exploration of soil microbial stoichiometry along an aridity gradient at the regional scale impedes our ability to disentangle the trend of the changes in microbial stoichiometry amid climate changes.…”
Section: Introductionmentioning
confidence: 99%
“…Climate could exert an influence on microbial stoichiometry through changes to the microenvironment, such as soil moisture and temperature, and it could also impact the availability of substrates in the soil (Nielsen et al, 2009). Moreover, edaphic variables, such as soil organic carbon (SOC; Maria et al, 2014;Chen et al, 2016) and soil texture (Li et al, 2015), could be associated with nutrient mineralization and availability, thus influencing the C : N : P stoichiometry in microbial biomass (Griffiths et al, 2012). A labeled incubation experiment showed that the mineralization of organic P was mainly driven by the microbial C demands in P-poor soils (Aponte et al, 2010;Heuck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation